ANALYSIS AND EVALUATION OF MEASURES TAKEN AT THE FEDERAL AND REGIONAL LEVELS OF GOVERNMENT FOR THE EXIT OF THE RUSSIAN ECONOMY FROM THE PANDEMIC - D. A. Kurapov; A. A. Konusova; E. A. Khalimon (Вестник университета)
The COVID-19 epidemic has become a serious challenge for the economies of all countries of the world. The consequences of the fight against the spread of the virus have led to serious complications in the Russian economy. This article analyses the measures taken by the federal and regional governments aimed at curbing the spread of the pandemic, as well as supporting the economy of Russia and its subjects. The paper presents foreign experience on the measures taken and a comparative analysis between the countries. In addition, the authors study the influence of government decisions and their effectiveness on the basis of scientific articles, estimates and statistics published in the mass media, forecasts of the Ministry of Economic Development of the Russian Federation, reports of the Federal State Statistic Service.